(3eUGOQ GdeYdheGJ GdEYdGejI (B/s - (3bfOjdLj, YGeQ GHQGgjes ((3YeGf (B:s (3OGQ GdeSjQI ,s, 2015)
(3GdeSDhdjI GdbGfhfjI (B- (3Mbhb GdEbJHGS (B- (3Mbhb GdfTQ(B- (3JhKjb GdeYdheGJ eUGOQ GdeYdheGJ (B- (3GdeYdheGJ GdEYdGejI (B- (3CfhGY GdeYdheGJs
Keywords: (3GdEYdGes; (3GdeYdheGJ GdEdcJQhfjI s; (3GdeYdheGJ GdhQbjI GdeWHhYIs; (3Mbhb GdfTQs